3D bioprinted hydrogel/polymer scaffold with factor delivery and mechanical support for growth plate injury repair - Fan, Minjie; Qiang, Lei; Wang, Yiwei; Liu, Yihao; Zhuang, Hanjie; Guo, Ruoyi; Ben, Yulong; Li, Qiang; Zheng, Pengfei (Frontiers in Bioengineering and Biotechnology, 2023)
Growth plate injury is a significant challenge in clinical practice, as it could severely affect the limb development of children, leading to limb deformity. Tissue engineering and 3D bioprinting technology have great potential in the repair and regeneration of injured growth plate, but there are still challenges associated with achieving successful repair outcomes. In this study, GelMA hydrogel containing PLGA microspheres loaded with chondrogenic factor PTH(1-34) was combined with BMSCs and Polycaprolactone (PCL) to develop the PTH(1-34)@PLGA/BMSCs/GelMA-PCL scaffold using bio-3D printing technology. The scaffold exhibited a three-dimensional interconnected porous network structure, good mechanical properties, biocompatibility, and was suitable for cell chondrogenic differentiation. And a rabbit model of growth plate injury was applied to validate the effect of scaffold on the repair of injured growth plate. The results showed that the scaffold was more effective than injectable hydrogel in promoting cartilage regeneration and reducing bone bridge formation. Moreover, the addition of PCL to the scaffold provided good mechanical support, significantly reducing limb deformities after growth plate injury compared with directly injected hydrogel. Accordingly, our study demonstrates the feasibility of using 3D printed scaffolds for treating growth plate injuries and could offer a new strategy for the development of growth plate tissue engineering therapy.